Database security: general and research perspectives - Islam, Md. Rafiqul (Penerbit UTM Press, 1996)
Since database technology is a necessity for many government as well as commercial organizations it is extremely important for the various communities to be aware of the developments made in securing database systems. Database security has been the subject of active research for the past several years. Rapid progress has been made in defining what security means for such systems and in developing laboratory prototypes and even products that meet those definitions. However, much more work remains to be done in key research area. This paper provides an overview of the database security including policies and models as well as security issues in various aspects are also given.